Photonic Crystal Fiber Modal Interferometer for Refractive Index Sensing - Daniel Kacik; Peter Tatar (Communications - Scientific letters of the University of Zilina, 2013)
We present a modification of core-cladding intermodal interferometer for refractive index sensing. Its structure consists of double cladding photonic crystal fiber (PCF) as a sensing element. First cladding allows fundamental mode propagation only. Second cladding consists of ring of holes with the average refractive index higher than the basic material of the fiber and it is situated close to interface fiber-external environments. So the cladding mode is confined in the ring of holes and its evanescent field extends to external environment. Advantages of this arrangement against core – cladding interferometers are higher sensitivity and, by suitable choice of refractive index of second cladding holes, the possibility to investigate the external refractive index in the region where phase constants of interfering modes shows an extreme (equalization wavelength) in the spectral region.